Cosmetic Topical Formulations: Design Strategies, Skin Interaction Mechanisms, Clinical–Cosmetic Applications, and Emerging Trends - Maaz Reza; Shafkat Hussain Malik; Tawqeer Shafi; Imtiyaz Hussain (Recent Trends in Cosmetics, 2026)
Cosmetic topical products are central to modern skin care, as they deliver active ingredients directly to the skin surface and upper layers to improve appearance, texture, and function. By acting locally on the epidermis and adnexal structures, these preparations help manage dryness, photoaging, pigmentation, acne, and sensitive-skin conditions while minimizing systemic exposure. A wide range of dosage forms—creams, lotions, gels, ointments, serums, sprays, and transdermal-inspired cosmetic patches—are engineered to modulate skin hydration, barrier function, and penetration of cosmetic or cosmeceutical actives. Recent advances in formulation science have introduced nanocarriers, vesicular systems, smart hydrogels, and bioactive dressings adapted for cosmetic use, improving stability, targeted delivery, sensorial properties, and consumer adherence. Nonetheless, cosmetic topical delivery faces challenges, including the strong barrier function of the stratum corneum, irritation risk, variability in skin condition, and the need to comply with cosmetic safety and regulatory standards. This review outlines skin structure relevant to cosmetic delivery, classification of cosmetic dosage forms, key formulation components, mechanisms of skin interaction and absorption, clinical–cosmetic applications, advantages, limitations, and recent innovations in cosmetic and cosmeceutical topical systems, highlighting their growing role in contemporary cosmetic science and practice.
Keywords: Cosmeceuticals; Cosmetic formulation; dermatological aesthetics; nanocosmetics; skin delivery; topical cosmetics